The European territory : from historical roots to global challenges - Robert, Jacques, 1947-2011 (Routledge, 2014)
"Originally published in French as Le territoire européen : des racines aux enjeux globaux, this book reflects the enormous changes that Europe has seen in the past half century. In a period of immense upheaval, the continent has experienced increased integration, largely through the development of the European Union, heightened urbanization and a changing rural landscape, while economic and commercial activities have impressed their stamp on the whole scene. In this book, Jacques Robert deploys the experience amassed throughout his 35 years' experience as adviser to European institutions in the field of territorial and regional development. The chapter on cities explains the emergence of the European urban hierarchy and the driving forces and inertia behind its evolution, while a following chapter looks at the changing role of rural areas. This material provides a historic overview of relevant policies and a discussion of future challenges. The third chapter discusses evolving paradigms of regional economic development and their impact on European regions. Next, there is a chapter on the historical roots and current processes within territorial integration. The book concludes with an examination of Europe's place in the world at large, focussing particularly on globalization effects, climate change and new energy paradigms, which will present real challenges for decades to come.The book is unique in its combination of in-depth analysis of the evolution of European territorial policies and paradigms, but also in its geographically comprehensive approach integrating the experience of both Western and Eastern Europe. It will be of interest to academics and professionals within territorial development and spatial planning"--Resumé vydavatele
Přeloženo z francouzštiny
Keywords: regionální rozvoj -- země Evropské unie; regionální politika -- země Evropské unie; ekonomický růst -- země Evropské unie; regionální rozdíly -- země Evropské unie; rozvoj měst -- země Evropské unie; místní rozvoj -- země Evropské unie; rozvoj venkova -- země Evropské unie; globalizace -- země Evropské unie; ekonomická integrace -- země Evropské unie; regional development -- European Union countries; regional policy -- European Union countries; economic development -- European Union countries; regional disparities -- European Union countries; urban development -- European Union countries; community development -- European Union countries; rural development -- European Union countries; globalization -- European Union countries; economic integration -- European Union countries; země Evropské unie -- hospodářské poměry; European Union countries -- economic conditions; monografie; monographs